Indian writing in English : a critical study - Agrawal, K.A. (New Delhi : Atlantic, 2003)
Contributed articles.
Includes bibliographical references.
DELL
Includes passages in Sanskrit.
Keywords: Indic literature (English) -- 20th century -- History and criticism